On the Mechanics of Economic Convergence - Thomas M. Steger (ETH Zurich, CER-ETH - Center of Economic Research, 2003)
In macroeconomic dynamic models the speed at which output converges to its steady state is of outstanding interest. Theoretical investigations usually focus on the asymptotic speed of convergence only. This procedure is, however, unnecessarily restrictive and hides important information. The paper at hand provides a straightforward and simple analytical decomposition of the instantaneous rate of convergence into its economic determinants. In addition, the resulting convergence-accounting formula is applied to analyse the transition process of a general R&D-based endogenous growth model. As a result, the driving forces behind the convergence process are identified.
Keywords: O0; O3; O31; O33; O41; 330; Convergence accounting; rate of convergence; decomposition; convergence mechanisms; R&D-based growth; Wirtschaftswachstum; Wirtschaftliche Konvergenz; Theorie